Comparative Analysis of ChatGPT Translation and Google Translate as a Medium for Learning Mandarin for Chinese Language Education Students Universitas Negeri Semarang - Daffa, Muhammad Farhan Afif; Pamuji, Dian Yuni (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to analyse the comparison of translation quality from Chinese to Indonesian produced by ChatGPT and Google Translate, as learning media for Chinese Language Education students. Using a qualitative approach and comparative descriptive method, this study analysed 20 sentences from textbooks translated by both platforms. The analysis was based on three main aspects: accuracy of meaning, fluency of language, and suitability of context. The results showed that ChatGPT is consistently superior in producing more fluid and contextual translations than Google Translate, which tends to be more literal. Although both tools can be utilised as a learning support medium, ChatGPT has proven to be of better quality. It was concluded that students need to keep using their linguistic understanding to critically evaluate translation Results.